DISPARITAS DAN KONVERGENSI PRODUK DOMESTIK REGIONAL BRUTO (PDRB) PER KAPITA ANTAR KABUPATEN/ KOTA DI PROVINSI BALI - Savitri Gama, Ayu (INPUT Jurnal Ekonomi dan Sosial; Vol. 1, No. 2 Februari 2009)
This research is aimed at analyzing regional disparity among regencies in Bali Province from 1993 up to 2006. Williamson’s weighted coefficient of variation is used to measure the regional disparity in Bali. Besides of regional disparity, this research has identified the convergence or divergence of PDRB per individual person, and also any factors that have been influencing the regional disparity and convergence. The result of analyzes indicates that there is an increasing regional disparity among regencies in Bali during 1993-2006. Many factors caused disparity are Lag PDRB Per Capyta, Investment Allocation, human capital, and employer. From the result of pooled data estimation, the Investment allocation influences the regional convergence.
Keywords: Disparity, Convergency, Williamson’s weighted coefficient